Human Resource Development Strategy On The Performance Of Grilled Fish UMKM In Tambak Wedi Surabaya : Swot Analysis - Sutomo, Sutomo; Churiyah, Madziatul (IJBLE Scientific Publications Community Inc., 2024)
The aim of this research is for​ know strategy development source Power man on the Performance of Grilled Fish MSMEs in Tambak Wedi through SWOT analysis This study uses a qualitative method. The data sources used are primary and secondary data. Data collection techniques using interviews and documentation. The data analysis used is SWOT analysis. Based on the results of research and discussions conducted by researchers regarding human resource development strategies to improve micro, small and medium enterprises (MSMEs) in Grilled Fish MSMEs in Tambak Wedi Village, the following conclusions can be drawn: New HR receives good guidance from senior HR and in accordance with existing regulations. HR can Study from training and contribute to the company. HR is expected to be able to produce Grilled Fish in accordance with consumer demand . Seniors are expected to be able to guide HR to deepen their work.